NGL-1/LRRC4C-Mutant Mice Display Hyperactivity and Anxiolytic-Like Behavior Associated With Widespread Suppression of Neuronal Activity - Choi, Yeonsoo; Park, Haram; Kang, Suwon; Jung, Hwajin; Kweon, Hanseul; Kim, Seoyeong; Choi, Ilsong; Lee, Soo Yeon; Choi, Ye-Eun; Lee, Seung-Hee; Kim, Eunjoon (Frontiers in Molecular Neuroscience, 2019)
Netrin-G ligand-1 (NGL-1), encoded by Lrrc4c, is a postsynaptic adhesion molecule implicated in various brain disorders, including bipolar disorder, autism spectrum disorder, and developmental delay. Although previous studies have explored the roles of NGL-1 in the regulation of synapse development and function, the importance of NGL 1 for specific behaviors and the nature of related neural circuits in mice remain unclear. Here, we report that mice lacking NGL-1 (Lrrc4c–/–) show strong hyperactivity and anxiolytic-like behavior. They also display impaired spatial and working memory, but normal object-recognition memory and social interaction. c-Fos staining under baseline and anxiety-inducing conditions revealed suppressed baseline neuronal activity as well as limited neuronal activation in widespread brain regions, including the anterior cingulate cortex, motor cortex, endopiriform nucleus, bed nuclei of the stria terminalis, and dentate gyrus. Neurons in the anterior cingulate cortex, motor cortex, and dentate gyrus exhibit distinct alterations in excitatory synaptic transmission and intrinsic neuronal excitability. These results suggest that NGL-1 is important for normal locomotor activity, anxiety-like behavior, and learning and memory, as well as synapse properties and excitability of neurons in widespread brain regions under baseline and anxiety-inducing conditions.